The influence of Internet of Things (loT) application in estate agency practice in Ipoh, Perak / Sarah Noor Jairin Jairi - Jairi, Sarah Noor Jairin (2023)
The Internet of Things refers to the interconnection of everyday objects with the internet, allowing them to send and receive data. loT technology has the potential to revolutionize numerous industries by providing enhanced connectivity, automation, and data-driven decision-making. In the context of estate agency practice, the integration of loT applications holds considerable promise to improve efficiency, customer experience, and overall operational effectiveness. However, there is a lack of comprehensive understanding regarding the types of loT technology currently utilized in the estate agency practice in the and the effectiveness of their application The influence of Internet of Things (loT) technology in real estate agency practices in lpoh, Perak was investigated in this research. The aim of this research is to study the types of lnternets of Things (loT) technology used among of the Estate Agency practice in lpoh, Perak, and its effectiveness. Therefore, the research objectives are to identify the types of lnternets of Things (loT) technology used in the estate agency practice and to analyse the effectiveness Of the Application of Internet of Things (loT) Technology in Real Estate Firm. The study was conducted among 30 respondents from estate agency firm using quantitative method.